Occupational licensing in Alabama. (3rd April 2017) - Smith, Daniel J.
ABSTRACT: While often advanced as a means to protect consumers, occupational licensing is increasingly being recognized as a barrier to entry that benefits the licensed industry to the detriment of consumers. Furthermore, it often restricts economic mobility, especially among minority groups. Given that occupational licensing is primarily carried out at the state level, state-specific analyses are required to understand the extent and impact of occupational licensing, as well as to inform national and state reform discussions. This paper provides an in-depth analyses of occupational licensing in Alabama and offers recommendations for reform.